In vitro immunosuppressive and cytotoxic activities of Tripterygium wilfordii extract. (April 2015) - He, Yu; Shi, Senlin; Zhang, Ruping; Shen, Wei; Tu, Jue; Ding, Zhishan; Fan, Yongsheng
Abstract Tripterygium wilfordii Hook. f. (TW) is a traditional herbal medicine which has been widely used for the treatment of rheumatoid arthritis and other autoimmune diseases. However, adverse reactions of TW such as hepatotoxicity and nephrotoxicity have been frequently reported in clinic. With the aim to evaluate the potency and toxicity of TW, we collected eleven batches of TW from different localities across Chinese mainland, and investigated the inhibition of their methanol extracts on the proliferation of mouse spleen lymphocytes, normal human hepatocyte (L-02) cells and African green monkey kidney (COS-7) cells. TW extracts with three different concentrations were designed as the experimental groups. Our present findings provided consistent evidence that TW had significant concentration-dependent inhibitory action on lymphocytes, L-02 and COS-7 cells. At the concentrations of 0.75 and 1.5 mg/mL, most TW groups showed statistically significant inhibition of lymphocyte proliferation when compared with the control group (p < 0.01), and the inhibition of TW extract on lymphocytes was almost equal to 1.0 mg/mL aspirin (p > 0.05). In most test groups, significant toxicities were shown on L-02 cells at 0.6 and 3.0 mg/mL (p < 0.01), and on COS-7 cells at 3.0 mg/mL (p < 0.01). At 3.0 mg/mL, almost all TW groups exerted obvious toxicities toward L-02 and COS-7 cells which were equal to or even higher than 1.0 mg/mL aspirin. In view of these results, further studies are needed to elucidate the relations among the effective component, curative effect and toxicity of TW to ensure its effectiveness and safety for human consumption.